2014
DOI: 10.1158/1055-9965.epi-13-0665
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Survival Outcomes in Cancer Patients with Hereditary Hemorrhagic Telangiectasia

Abstract: Background Hereditary hemorrhagic telangiectasia (HHT) is a genetic disorder characterized by deficiency in endoglin, an angiogenic protein. The net effect of endoglin expression on cancer outcomes from animal studies has proven controversial. We evaluated whether reduced systemic endoglin levels, expected in patients diagnosed with HHT, impacted clinical outcomes for cancer. Methods A retrospective cohort analysis using SEER-Medicare was conducted to evaluate the effect of HHT on survival among patients dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
0
24
1
1
Order By: Relevance
“…Patients with HHT often tolerate anticoagulation or antiplatelet therapy well 49. Recently described reduced rates of specific cancers,34 50 51 better survival outcomes for cancer patients who have HHT52 and low myocardial infarction rates20 await explanation. The HHT phenotype is subtly different between HHT genotypes, for instance patients with HHT2 are less likely to have PAVMs and more likely to have hepatic AVMs than patients with HHT1 or SMAD4 -related HHT 37 39.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HHT often tolerate anticoagulation or antiplatelet therapy well 49. Recently described reduced rates of specific cancers,34 50 51 better survival outcomes for cancer patients who have HHT52 and low myocardial infarction rates20 await explanation. The HHT phenotype is subtly different between HHT genotypes, for instance patients with HHT2 are less likely to have PAVMs and more likely to have hepatic AVMs than patients with HHT1 or SMAD4 -related HHT 37 39.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is an interesting question of whether HHT manifests cancer-prone phenotypes or not. A clinical observational study demonstrated that reduced endoglin expression in HHT is associated with a lower frequency of common malignancies, including lung, prostate and colorectal cancer, and a more favorable cancer-specific survival (10). Based on these findings, the current patient's case is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses have revealed that abnormalities in endoglin family genes cause HHT (10). In an in vivo experiment, the overexpression of endoglins in prostate cancer cells revealed growth-inhibiting effects on tumor cells (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Following demonstration of better survival outcomes for HHT cancer patients (Duarte 2014), the authors examined cancer incidence, pooling lung, breast, prostate and colorectal cancer. Using a general population registry, 316,581 matched cancer patients and non-cancer controls were identified, including 219 and 212 HHT cases respectively.…”
Section: To the Editormentioning
confidence: 99%